Effect of different formulation on efficiency of honey effervescence tablet / Muhammad Mohd Kaharuddin - Mohd Kaharuddin, Muhammad (2023)
Honey has been utilized by humans for a very long time, both traditionally and in modern ways. This is due to honey's many benefits, which make it one of the most sought-after foods and medicines globally. Its benefits include a great source of carbohydrates, acting as a natural antioxidant to prevent or delay most cell damage, acting as an antibacterial because of its antioxidant, anti-bacterial, and anti- inflammatory properties, reduce headache and many more. However, usual way of consuming honey such as raw is proven to be quite taxing and quite unpleasing. One of the ways to solve this are to prepare stingless honeybee effervescent tablet as it is convenient to be brought anywhere, easy to digest and great choice for those who have difficulties in swallowing honey directly. 5g of diluted stingless honeybee are tested to determine its physiochemical properties such as pH, moisture content, hygroscopicity and refractive index which are average around 3.9, 15.62%, 16.58 and 1.45 respectively. Three different formulations have been prepared to test efficiency of stingless honeybee effervescent tablet with different formulation namely formulation one (F1) sodium bicarbonate 1.00g and citric acid 1.00g, formulation two (F2) sodium bicarbonate 1.00g, citric acid 1.50 g and formulation three (F3) sodium bicarbonate 3.44g, citric acid 1.44 g and 1.65 g tartaric acid. The efficiency of tablets is determined by effervescence time, pH and solubility of the tablets.